La parole aux images, ou Multilinguisme et traduction dans les films de John McTiernan - Agiboust, Sylvain (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Most of modern Hollywood action movies are Manichean and ethnocentric but John McTiernan’s films are surprisingly scrupulous in the depiction of other cultures and the use of foreign languages. The director first uses theses languages for their musicality and exotic feeling. The ability to speak is depicted as the main characteristic of humanity. The understanding of the other one is based on the knowledge of its language, so the interpreter became a very important role in McTiernan’s movies. The interpreter’s character appears as a link between the individuals, wrangled over their own language and culture. The interpreter is also standing for the spectator and leads him into unknown worlds. John McTiernan does not only make movies about interpreters. The act of translation appears to be the one of the most important aspects of his cinematographic style. McTiernan considers spoken words mostly as noises and thinks that the real meaning of the movie is delivered by the pictures themselves: the expressivity of cinema is the one of framing and camera moves. The audience may not understand the language spoken by the characters but he can always rely on the pictures, which are meaningful. McTiernan’s mise en scene becomes a substitute for spoken language.